Features of a Course of General Tuberculosis in Adolescents - O.M. Raznatovska; Yu.V. Myronchuk; L.I. Chernyshova; N.I. Subbotina; O.O. Pushnova (Zaslavsky O.Yu., 2016)
The feature of a course of tuberculosis in adolescence is the tendency to progression, necrotic reactions. The most severe outcome of general specific process is the development of meningitis, which can often be its end stage. Objective - to study the peculiarities of a course of general tuberculosis combined with tuberculous meningitis in an adolescent on the example of a clinical case. The features of a course of general tuberculosis associated with tuberculous meningitis in an adolescent were: the development of adverse reactions to long-term combination antituberculous treatment and hormone therapy (toxic hepatitis, Cushing's disease of secondary origin); complication of tuberculous meningitis by ischemic stroke in the subcortical regions of the left hemisphere of the great brain and descending optic nerve atrophy; a positive dynamics when the regimen of antituberculosis chemotherapy is selected properly as the manifestations of both general tuberculosis and specific meningitis.